Antecedents of Usefulness of Electronic Word of Mouth (E-WOM) Information on Consumer’s Purchase Intention - Aini, Saqofa Nabilah; Nugroho, Sahid Susilo (Ekonomi Bisnis, 2021)
This study examines the effect of communication through social media (electronic word of mouth) on consumer’s purchase intentions. This research model was developed from the theory of information adoption model. The study was conducted by quantitative approach through survey method. The data collection process is done online, with the sample size reaching 240 respondents. The data analysis method used to test the relationship between variables in this study is regression analysis. The study findings show that source credibility, source perceptions, two-sided information, and information ratings positively and significantly impact the usefulness of electronic word-of-mouth information. In comparison, the argument quality does not affect the usefulness of electronic word-of-mouth information. The usage variable of the information of active viral influence has a positive and significant effect on the adoption information of electronics word-of-mouth, which has a positive and significant effect on consumer purchase intentions.